AMP‐activated protein kinase (AMPK) activator A‐769662 increases intracellular calcium and ATP release from astrocytes in an AMPK‐independent manner. Issue 7 (21st April 2017) - Vlachaki Walker, Julia M.; Robb, Josephine L.; Cruz, Ana M.; Malhi, Amrinder; Weightman Potter, Paul G.; Ashford, Michael L. J.; McCrimmon, Rory J.; Ellacott, Kate L. J.; Beall, Craig
Abstract : Aim: To test the hypothesis that, given the role of AMP‐activated protein kinase (AMPK) in regulating intracellular ATP levels, AMPK may alter ATP release from astrocytes, the main sources of extracellular ATP (eATP) within the brain. Materials and Methods: Measurements of ATP release were made from human U373 astrocytoma cells, primary mouse hypothalamic (HTAS) and cortical astrocytes (CRTAS) and wild‐type and AMPK α1/α2 null mouse embryonic fibroblasts (MEFs). Cells were treated with drugs known to modulate AMPK activity: A‐769662, AICAR and metformin, for up to 3 hours. Intracellular calcium was measured using Fluo4 and Fura‐2 calcium‐sensitive fluorescent dyes. Results: In U373 cells, A‐769662 (100 μM) increased AMPK phosphorylation, whereas AICAR and metformin (1 mM) induced a modest increase or had no effect, respectively. Only A‐769662 increased eATP levels, and this was partially blocked by AMPK inhibitor Compound C. A‐769662‐induced increases in eATP were preserved in AMPK α1/α2 null MEF cells. A‐769662 increased intracellular calcium in U373, HTAS and CRTAS cells and chelation of intracellular calcium using BAPTA‐AM reduced A‐769662‐induced eATP levels. A‐769662 also increased ATP release from a number of other central and peripheral endocrine cell types. Conclusions: AMPK is required to maintain basal eATP levels but is not required for A‐769662‐induced increases in eATP. A‐769662 (>50 μM) enhanced intracellular calcium levels leading to ATP release in an AMPK and purinergic receptor independent pathway.